+0  
 
0
203
2
avatar

how do you simplify 5 - (2x + 3)

Guest Sep 12, 2017
 #1
avatar
0

5-2x -3 

2x=5+3

2x=8

x=8:2 

x=4

Guest Sep 12, 2017
 #2
avatar+87301 
+1

 5 - (2x + 3)  =

 

5 - 2x  - 3   =

 

2 - 2x

 

 

cool cool cool

CPhill  Sep 12, 2017

7 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.